Implementation of Occupational Drawing Therapy in Auditory Hallucination Patients - Valendra, Kelvin; Yunitasari, Pritta; Purwaningsih, Iswanti (Global Health Science Group, 2024)
Hallucinations are unreal sensory perception disorders that a person experiences. Signs and symptoms of hallucinations are examples of hearing unreal voices, talking to themselves, worrying, and suspicious which one can endanger themselves or others if someone follows the hallucinations. Management that can be carried out is non-pharmacological therapy with drawing occupational therapy. Objective: To determine the change in hallucination rate and signs of hallucinatory symptoms. After occupational therapy, drawing was carried out in patients with auditory hallucinations. Methods: In this case study using a descriptive case study, the subject of the case study was taken 1 respondent according to the inclusion criteria. The instruments used in this case study are SOP, occupational therapy, drawing, Audiotory, Hallucination Rating Scale (AHRS), observation sheet, signs and symptoms of hallucinations. The data collection method is by conducting interviews, observations, the application of occupational therapy, drawing, evaluation, and documentation. Results: The application of drawing occupational therapy was carried out on 1 respondent, namely Ms. C, before the treatment was carried out, the patient received an AHRS score of 21 and 7 on the observation of signs and symptoms of hallucinations. After the therapy, the patient obtained an AHRS score of 9, and a score of 1 on the observation of signs and symptoms of hallucinations. Conclusion: Occupational drawing therapy may lower hallucinations rates and signs and symptoms of auditory hallucinations